Perencanaan Sarana Dan Prasarana Di Sekolah Dasar Islam Mohammad Hatta Malang - Zakiyah Alvi Rochmania (Leadership: Jurnal Mahasiswa Manajemen Pendidikan Islam, 2021)
Management as a tool to assist in any activity, such as in the world of education, as the elements contained in management, namely: planning, organizing, implementing, and evaluating. The existence of a management refers more to certain fields, for example in the management of facilities and infrastructure. Management of facilities and infrastructure that regulates facilities and support for school residents to carry out teaching and learning activities. Meanwhile, the facilities and infrastructure before the pandemic and when the pandemic still existed, must have experienced differences. Good facilities and infrastructure need to be prioritized with a plan, planning contained in the management of facilities and infrastructure has one point, namely the existence of a RKAS. RKAS is a plan regarding funds that will be used for school development.